About the Project
NIST

products

AdvancedHelp

(0.001 seconds)

1—10 of 172 matching pages

1: 30.10 Series and Integrals
For product formulas and convolutions see Connett et al. (1993). …For expansions in products of spherical Bessel functions, see Flammer (1957, Chapter 6).
2: 13.12 Products
§13.12 Products
For integral representations, integrals, and series containing products of M ( a , b , z ) and U ( a , b , z ) see Erdélyi et al. (1953a, §6.15.3).
3: 13.25 Products
§13.25 Products
For integral representations, integrals, and series containing products of M κ , μ ( z ) and W κ , μ ( z ) see Erdélyi et al. (1953a, §6.15.3).
4: 27.4 Euler Products and Dirichlet Series
§27.4 Euler Products and Dirichlet Series
The fundamental theorem of arithmetic is linked to analysis through the concept of the Euler product. …In this case the infinite product on the right (extended over all primes p ) is also absolutely convergent and is called the Euler product of the series. If f ( n ) is completely multiplicative, then each factor in the product is a geometric series and the Euler product becomes … Euler products are used to find series that generate many functions of multiplicative number theory. …
5: 4.22 Infinite Products and Partial Fractions
§4.22 Infinite Products and Partial Fractions
4.22.1 sin z = z n = 1 ( 1 - z 2 n 2 π 2 ) ,
4.22.2 cos z = n = 1 ( 1 - 4 z 2 ( 2 n - 1 ) 2 π 2 ) .
6: 4.36 Infinite Products and Partial Fractions
§4.36 Infinite Products and Partial Fractions
4.36.1 sinh z = z n = 1 ( 1 + z 2 n 2 π 2 ) ,
4.36.2 cosh z = n = 1 ( 1 + 4 z 2 ( 2 n - 1 ) 2 π 2 ) .
7: 20.5 Infinite Products and Related Results
§20.5 Infinite Products and Related Results
§20.5(i) Single Products
Jacobi’s Triple Product
§20.5(iii) Double Products
8: 10.28 Wronskians and Cross-Products
§10.28 Wronskians and Cross-Products
9: 10.63 Recurrence Relations and Derivatives
§10.63(ii) Cross-Products
10.63.7 p ν s ν = r ν 2 + q ν 2 .
10: 26.12 Plane Partitions
26.12.4 ( h , j , k ) B ( r , s , t ) h + j + k - 1 h + j + k - 2 = h = 1 r j = 1 s h + j + t - 1 h + j - 1 .
26.12.10 ( h = 1 r j = 1 s h + j + t - 1 h + j - 1 ) ( h = 1 r + 1 j = 1 s h + j + t - 1 h + j - 1 ) ;
26.12.11 ( h = 1 r + 1 j = 1 s h + j + t - 1 h + j - 1 ) ( h = 1 r j = 1 s + 1 h + j + t - 1 h + j - 1 ) .
26.12.13 h = 1 r j = 1 r h + j + t - 1 h + j - 1 ;
26.12.14 h = 1 r j = 1 r + 1 h + j + t - 1 h + j - 1 .